Peningkatan Kemampuan Membaca Teks Recount dengan Model Pembelajaran Jigsaw melalui Gambar “Sungai Kehidupan” - Erna Pujiasih (Ideguru: Jurnal Karya Ilmiah Guru, 2021)
This research aims to increase reading ability of recount text. The research is done because only 43% students who passed reading test. Subject of research was 36 students in class of XI IPS 2 SMA Negeri 1 Bantul. The are two cycles in conducting a classroom action. Every cycles consist of planning, action, observation, and reflection in jigsaw learning model. The data of research are observation, questioner, test and interview in understanding recount text with “sungai kehidupan” which is related to biography and historical recount through jigsaw learning model. Based on the test result obtained increasing reading ability from 42% to 83%, response data of learning are 0.6% of students very agree, 80% agree and 9,4% disagree. From questioner, students can understand the text, enjoying, variety, effective, creative, cooperation, critical thinking, and fascinating in learning. This learning model is very useful for students so they can interest in studying, variety of teaching and suitable for teacher to teach recount text with “sungai kehidupan”.